Integrating Conservation and Development in Southern Western Ghats of Kerala, India: Achievements, Challenges and Opportunities - Bhardwaj, Aditi (Indian Forester, 2019)
Ecodevelopment, a co-management model, is a site-specific approach, which seeks active community participation and ownership for the twin objectives of conservation and development in and around Protected Areas (PAs). The last three decades of implementation of this approach in different PAs of India have given mixed results. This study, carried out in three important PAs of Southern Western Ghats in Kerala, tries to evaluate the programme, present a people's perspective on the issue of conservation and development and highlights the emerging challenges for effectively carrying forward these initiatives. Study employs a mixed approach to qualitative and quantitative assessment through surveys, focused group discussions and in-depth interviews with different Ecodevelopment Committees. The study reveals that while the programme has been largely successful in achieving its objectives, there are variations primarily in terms of secondary benefits, which could be attributed to the varying extent of handholding and strength of institutional frameworks in the three sites. Moreover, there are newer challenges that are emerging which call for a dynamic and flexible outlook towards continuation of these initiatives.